Tax transparency and abusive practices in double taxation agreements: Evasion, avoidance and treaty strategies in Ecuador, 2025 - Paredes Sánchez, Katherine Estefanía (2025)
Treaty shopping, tax evasion, and tax avoidance strategies represent significant challenges to Ecuador's tax sustainability. These practices, used by multinational companies and large taxpayers, allow for the artificial reduction of the tax burden through the manipulation of double taxation agreements (DTAs) and other forms of aggressive tax planning. This article seeks to evaluate the effect of various measures on tax revenues and assess the effectiveness of the measures implemented at the national and global levels to mitigate their effects. Through a systematic documentary review of scientific studies, reports from international organizations, and data from the Internal Revenue Service (IRS), it was identified that tax evasion and avoidance undermine the equity of the tax structure and diminish the State's capacity to invest in essential public services. Although Ecuador has adopted some actions from the OECD BEPS Plan, such as transfer pricing control and the regulation of transactions between related parties, regulatory and operational gaps still persist that allow these practices to continue. It is concluded that it is necessary to strengthen enforcement, implement stricter regulations in the DTTs, and improve global cooperation to reduce the negative impacts of these strategies.